Uso de vancomicina como tratamiento empírico en pacientes del servicio de UCI-neonatal del Hospital Nacional Edgardo Rebagliati Martins, junio – agosto 2016 - Ricardo Floriano, Ericka Milagros (2019)
This report of pre-professional practices aims to characterize the use of vancomycin as an empirical treatment in patients of the UCI-neonatology service of the Edgardo Rebagliati Martins National Hospital in the months of june, july and august 2016. The database of the Hospital management system and prescriptions of hospitalized patients to identify pathologies. The results of 38 patients were: 15 patients with sepsis, 5 patients with congenital malformations, 8 patients with meningitis, 1 patient with hydrocephalus, 3 patients with pneumonia, 2 patients with hypoxia, 2 patients with primary atelectasis and 2 patients with extreme immaturity. Sepsis being the diagnosis that was used for a greater number of days with a greater number of patients.